Reporter assays - Ceriani, Maria Fernanda (2007)
Transcriptional feedback loops are at the core of the molecular clockworks. As single clock genes were cloned it was compelling to develop an assay that allowed simple and direct functional testing of putative activators or repressors of transcription. This chapter includes a general description and guidelines to carry out transcriptional assays in transiently transfected Schneider's cells